"Do You Call Yourself a White Man?": Nationalism, Criminalization of Interracial Sex, and the Policing of White Male (Hetero)sexuality in South Africa during Apartheid. Issue 1 (26th April 2022) - Klausen, Susanne M
Abstract: This essay is about the policing of white male heterosexuality in order to protect whites' mythical racial purity in South Africa during the apartheid era (1948–94). Contrary to colonial authorities' practice of turning a blind eye to settler men's extramarital sexual exploits with colonized women, the apartheid regime attacked white heterosexual men's patriarchal sexual liberties. In 1950, the National Party government passed the Immorality Amendment Act criminalizing extramarital sex between whites and people of color. Though technically gender neutral, the law was crafted by leaders of the authoritarian and puritanical Afrikaner nationalist movement to stop white heterosexual men from crossing the color line for illicit sex. Tens of thousands of people were arrested for contravening the law, and while its enforcement inflicted tremendous harm and hardship on women of color, it was white men, often Afrikaner themselves, who made up the single largest category of individuals prosecuted and convicted. This essay examines the origins of the law, state methods of enforcement, and some of the harmful gendered social consequences of its brutal application.